Inflammation and post‐traumatic stress disorder - Hori, Hiroaki; Kim, Yoshiharu (Psychiatry and clinical neurosciences, 2019)
While post‐traumatic stress disorder (PTSD) is currently diagnosed based solely on classic psychological and behavioral symptoms, a growing body of evidence has highlighted a link between this disorder and alterations in the immune and inflammatory systems. Epidemiological studies have demonstrated that PTSD is associated with significantly increased rates of physical comorbidities in which immune dysregulation is involved, such as metabolic syndrome, atherosclerotic cardiovascular disease, and autoimmune diseases. In line with this, a number of blood biomarker studies have reported that compared to healthy controls, individuals with PTSD exhibit significantly elevated levels of proinflammatory markers, such as interleukin‐1β, interleukin‐6, tumor necrosis factor‐α, and C‐reactive protein. Moreover, various lines of animal and human research have suggested that inflammation is not only associated with PTSD but also can play an important role in its pathogenesis and pathophysiology. In this review, we first summarize evidence suggestive of increased inflammation in PTSD. We then examine findings that suggest possible mechanisms of inflammation in this disorder in terms of two different but interrelated perspectives: putative causes of increased proinflammatory activities and potential consequences that inflammation generates. Given that there is currently a dearth of treatment options for PTSD, possibilities of new therapeutic approaches using pharmacological and non‐pharmacological treatments/interventions that have anti‐inflammatory effects are also discussed. Despite the increasing attention given to the inflammatory pathology of PTSD, there remains much to be elucidated, including more detailed mechanisms of inflammation, potential usefulness of inflammatory biomarkers as diagnostic and prognostic markers, and efficacy of novel treatment strategies targeting inflammation.